Expression of Nuclear Receptor Coactivators in the Human Fetal Membranes at Term before and after Labor - Che-Wei Ryan Ou; Meihua Sun; Weronika Sadej; William Gibb (Obstetrics and Gynecology International)
Human fetal membranes play an important role in term and preterm labor and are responsive to steroids. We examined the expression of steroid receptor coactivators in fetal membranes obtained prior to and following labor at term. Proteins were localized by immunohistochemistry, Western analysis was carried out in nuclear extracts, and mRNA levels were determined by real-time RT-PCR. SRC-1, SRC-2, p300, and PCAF proteins were present in all nuclear extracts. The amnion nuclei expressed higher levels of SRC-1, p300, and PCAF than nuclei from the chorion-decidua, whereas the reverse was true for SRC-2. Chorion-decidua from patients before labor expressed higher levels of SRC-1 than those from patients after labor. Also, the PCAF level was higher in the amnion obtained before labor than the same tissue obtained after labor. In contrast to the protein expression, mRNA levels of SRC-1 and p300 were higher in the chorion-decidua compared to the amnion, whereas there was no difference in levels of SRC-2 and PCAF mRNAs between these two tissues. These data underline that the regulation of the expression of the coactivators in these tissues occurs during labor and is complex and tissue specific.